Оцінка ефективності діяльності підприємства на основі структурних складових собівартості продукції - Косенко, Андрій Васильович; Косенко, Олександра Петрівна; Єршова, Наталя Юріївна; Мащенко, Марина Анатоліївна; Погорєлов, Сергій Миколайович (Національний технічний університет "Харківський політехнічний інститут", 2024)
У статті досліджується проблема підвищення ефективності діяльності підприємств на основі аналізу структурних складових собівартості продукції. Визначено, що в умовах зростаючої конкуренції та ресурсних обмежень питання управління витратами набуває стратегічного значення. Обґрунтовано важливість системного підходу до оцінки собівартості не лише як загального показника, а як сукупності взаємопов’язаних елементів, окрема прямих матеріальних витрат, оплати праці, енерговитрат, амортизаційних нарахувань тощо. Проаналізовано сучасні методи контролю та управління витратами, які успішно застосовуються як у вітчизняній, так і в зарубіжній практиці. Особливу увагу приділено дослідженню ефективності діяльності підприємств із використанням DEA-моделей, що дозволяють кількісно оцінити ефективність використання ресурсів і виявити слабкі ланки в системі управління витратами

The article investigates the problem of increasing the efficiency of enterprises on the basis of the analysis of structural components of the cost of production. It is determined that in the conditions of growing competition and resource constraints, the issue of cost management acquires strategic importance. The importance of a systematic approach to cost estimation not only as a general indicator, but as a set of interrelated elements, in particular direct material costs, labor remuneration, energy costs, depreciation charges, etc., has been substantiated. Modern methods of control and management of costs, which are successfully applied both in domestic and foreign practice, are analyzed. Particular attention is paid to the study of the efficiency of enterprises using DEA models, which allow quantifying the efficiency of resource use and identifying weak links in the cost management system. The article also considers examples of the implementation of strategic cost management in manufacturing companies, in particular using forecasting technologies and combined analytical models. The results of the analysis of both Ukrainian and international scientific publications are presented, which indicate the relevance and prospects of using the structural approach to cost management in modern conditions. On the basis of the study, recommendations are formulated for the implementation of efficiency assessment mechanisms aimed at increasing profitability, reducing costs and ensuring sustainable development of the enterprise. The results can be used in the practical activities of managers, economists, financial analysts, as well as in the educational process.
Assessment of the efficiency of the enterprise based on the structural components of the cost of production
Keywords: ефективність; економічна оцінка; собівартість продукції; формування собівартості; промислові підприємства; витрати; ресурси; efficiency; economic assessment; cost of production; methods of formation; industrial enterprise; costs; resources